Presidential elections - Russia 2012 - Frolova, Ksenia; Dvořáková, Vladimíra, 1957-; Cibulková, Petra, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
The uniqueness of 2012 Presidential election campaign lies in some new trends: for the first time Internet played such an important role in influencing voters. It's not just about traditional official websites of the candidates, but first and foremost about campaigning in blogs and social networks. The opposition, including "off-system" one (which is advocating the overthrow of the ruling elite), was much more active in this field. The Internet space became the scene of this conflict, and we should expect that it would only escalate in the future.
Vedoucí práce: Vladimíra Dvořáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses